The Genesis of doctrinal studies of the duties of the state - Matviychuk, A.V. (Bulletin of the Karaganda University “Law Series”, 2018)
The relevance of this research work lies in the fact that in legal science the question of the doctrinal studies, the duties of the state is actually explored. It is also established that a number of other important issues such as theoretical framework for the understanding of state responsibilities, the establishment of the constitutional responsibilities of the state, the concept and specifics of such constitutional obligations, their types, legal regulation of the duties of the state security, not adequately reflected in natsionalnoy and foreign doctrinal jurisprudence. This article was researched and analyzed different points of view of philosophers, scientists and statesmen of the period, a New history, because this period brought some doctrinal justification in the aspect of research question responsibilities of the state. It was concluded that the objective prerequisite for the formation of legal concepts (secular, religious, monarchist, anti-monarchist, absolutistic, constitutional) about the responsibilities of the state has become historical, economic, political development of the society, in which were formed the States of the new format (centralized, absolutist, constitutional). Established that States the period of the New history was a task, which was to streamline state government in new format the public relations. An example of such rationalization was the doctrinal rationale for the rule of law that gives certain constitutional obligations, the performance of which was guaranteed by the сonstitution of the state